Fatigue Crack Growth in Maraging Steel Obtained by Selective Laser Melting - Antunes, Fernando (2019)
Selective Laser Melting (SLM) is an additive manufacturing technology, ideal for the production of complex-shaped components. Design against fatigue is fundamental in the presence of cyclic loads, particularly for these materials which typically have significant porosity, high surface roughness and residual stresses. The main objective here is to study fatigue crack growth (FCG) in the 18Ni300 steel obtained by SLM. Typical da/dN-DK curves were obtained in C(T) specimens, indicating that cyclic plastic deformation may be the controlling mechanism. A complementary analysis, based on plastic CTOD range, showed a relatively low level of crack tip plastic deformation, and consequently a reduced level of plasticity induced crack closure. The curve da/dN versus plastic CTOD range is clearly above the curves for other materials.